2008
DOI: 10.2111/07-059.1
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Plant Species Diversity: Influence of Roads and Prescribed Fire in Arizona Ponderosa Pine Forests

Abstract: Many studies have investigated the ecological effects of roads and roadsides as both habitat and dispersal corridors for exotic plant species. Several of these compared roadside exotic species richness and abundance with adjacent interior habitats, but we found no studies of individual exotic species' abundance between the two habitats in the context of prescribed fire. We measured exotic species richness and individual species' abundance along roadsides and in adjacent interior habitat (. 150 m) before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
(48 reference statements)
1
17
0
Order By: Relevance
“…Previous research has shown that linear disturbances and developments may act as corridors for nonnative species introduction and as nodes for expansion (Tyser and Worley 1992;Gelbard and Belnap 2003;Potito and Beatty 2005;Fowler et al 2008;Morgan and Carnegie 2009). When examining major types and the factors within the types, we found similar results: cheatgrass is more abundant in areas of human disturbance (i.e., roads and developments), though factors within the major types, such as vegetation type, fire, and aspect, also influence its abundance.…”
Section: Discussionsupporting
confidence: 74%
“…Previous research has shown that linear disturbances and developments may act as corridors for nonnative species introduction and as nodes for expansion (Tyser and Worley 1992;Gelbard and Belnap 2003;Potito and Beatty 2005;Fowler et al 2008;Morgan and Carnegie 2009). When examining major types and the factors within the types, we found similar results: cheatgrass is more abundant in areas of human disturbance (i.e., roads and developments), though factors within the major types, such as vegetation type, fire, and aspect, also influence its abundance.…”
Section: Discussionsupporting
confidence: 74%
“…Cheatgrass is an especially problematic exotic annual that can reduce function by establishing early in the growing season and becoming a persistent member of the plant community, providing continuous fine fuel that can increase fire frequencies (Brooks et al, 2004). It has been shown that many forms of disturbance can promote invasions by non-native plant species (Hobbs and Huenneke, 1992;Korb et al, 2004;Fowler et al, 2008). Over 50% of the exotic species we observed were designated as 'noxious weeds' in both treatment types, with the potential to negatively impact native plant communities (Sieg et al, 2003) (see spp.…”
Section: Ecosystem Responses To Mechanical Masticationmentioning
confidence: 99%
“…forests of the American West (Crawford et al 2001;Keeley and McGinnis 2007;Laughlin and Fulé 2008;McGlone et al 2009b). This prevalence is associated with recent increases in fire and anthropogenic disturbance in ponderosa pine forests (Gildar et al 2004;Keeley 2006;Fowler et al 2008). In 2002-2003, a ponderosa pine forest ecological restoration project in the Uinkaret Mountains of northern Arizona became heavily invaded by cheatgrass immediately following a severe drought and wet autumn and winter (McGlone et al 2009a).…”
Section: Introductionmentioning
confidence: 99%